A Comparison of the physiological demands of wheelchair basketball and wheelchair tennis - Croft, L.; Dybrus, S.; Lenton, J.; Goosey-Tolfrey, V. L. (International Journal of Sports Physiology and Performance, 2010)
Purpose: To examine the physiological profiles of wheelchair basketball and tennis and specifically to: (a) identify if there are differences in the physiological profiles of wheelchair basketball and tennis players of a similar playing standard, (b) to determine whether the competitive physiological demands of these sports differed (c) and to explore the relationship between the blood lactate [Bla-] response to exercise and to identify the sport specific heart rate (HR) training zones. Methods: Six elite athletes (4 male, 2 female) from each sport performed a submaximal and VO2peak test in their sport specific wheelchair. Heart rate, VO2, and [Bla-] were measured. Heart rate was monitored during international competitions and VO2 was calculated from this using linear regression equations. Individual HR training zones were identified from the [Bla-] profile and time spent within these zones was calculated for each match. Results: Despite no differences in the laboratory assessment of HRpeak, the VO2peak was higher for the basketball players when compared with the tennis players (2.98 ± 0.91 vs 2.06 ± 0.71; P = .08). Average match HR (163 ± 11 vs 146 ± 16 beats/min; P = .06) and average VO2 (2.26 ± 0.06 vs 1.36 ± 0.42 L/min; P = .02) were higher during actual playing time of basketball when compared with whole tennis play. Consequently, differences in the time spent in the different training zones within and between the two sports existed (P < .05). Conclusions: Wheelchair basketball requires predominately high-intensity training, whereas tennis training requires training across the exercise intensity spectrum.